Robot-assisted and thoracoscopic surgery in the treatment of patients with tumors of the thymus gland - P. S. Vetshev; A. Yu. Ablitsov; A. G. Sanadze; Yu. A. Ablitsov; V. I. Vasilashko; V. S. Kryachko; P. A. Lukyanov; B. A. Magomedov (Медицинский вестник Юга России, 2018)
Objective: Comparative analysis of the results of surgical treatment of patients with tumors of the thymus gland via sternotomy and thoracotomy (ST), videothoracoscopic (VTS) and the robotic-assisted (RA) interventions. Materials and methods: Th e results of surgical treatment of 138 patients with tumors of the thymus gland (TG) were analyzed TS was performed in 78 patients, VTS – 47, RA – 13. Th ere were 65 men, 73 women. Th e average age of patients was 50,5±12,7 years (from 19 to 81 years). Results: Intervention time of thymomthymectomy (TTE) by ST amounted to 91.2±33,4 min, VTS of 93.6±25,5 min, RA – 142,7±26,9 min. Aft er ST 6 (7.7%) patients had complications in the postoperative period, 2 (2.6%) fatal outcome. Aft er VTS in one patient complicated post-operative course. Th e duration of stay of the patient in hospital aft er ST TTE was 10.1±3.6 days, VTS – 6.6±1.9 days, RA – 6.3±1.4 days. Loco-regional recurrence and progression of the disease in the remote period were not revealed. Good eff ects (A and b) aft er the VTS TTE achieved at 20.0% of cases in RA at 27.3%, while ST TTE 8.4% of cases. Conclusion: Demonstrated safety and effi  cacy of minimally invasive techniques (MIT) in the surgical treatment of patients with thymoma. As were the advantages of the VTS and RA when performing TTE in comparison with ST.